인공지능 기반 시선 추적 기법을 활용한 모바일 커머스 사용자 시선 데이터 분석 - 김서영(Seoyeong Kim); 장지인(Jiin Jang); 박태정(Taejung Park) (디지털콘텐츠학회논문지, 2023)
본 연구에서는 별도의 시선 추적용 전용 하드웨어 장비 없이 일반적인 모바일 기기와 인공지능으로 시선 추적이 가능한 기술을 기반으로 모바일 커머스 이용 과정에서 사용자의 시선 데이터를 수집하여 관심 영역별로 분석하고, 그 결과를 소비자 분석을 위한 정량적인 지표와 직관적인 정보 시각화로 나타낼 수 있음을 증명하기 위한 구현 사례와 실험 결과를 제시한다. 제안하는 방법은 시선 데이터 전처리, 주시 특성에 따른 구분 과정, 응시한 지점들의 관심 영역별 통계 처리, 정보 시각화 과정으로 구성된다. 제안하는 방법은 고가의 전용 하드웨어 장비의 구입, 설치, 착용이 필수적인 기존 방법에 비해 저렴한 비용으로 접근 가능하며 일반적인 스마트폰이나 태블릿을 보유한 다수의 사용자가 시간과 공간의 제약 없이 자연스럽게 모바일커머스 환경을 이용하는 과정 중에서 필요한 정보를 추출할 수 있다. 따라서 기존에는 불가능했던 수준의 대규모 구매 과정에 대해 보다 구체적인 시선 정보 기반 데이터를 수집하고 분석할 수 있는 차별성을 제공한다. In this study, we implemented a system where the user gaze data were collected while they engaged in mobile commerce, and these data were analyzed based on the area of interest. The system is based on a technology that enables gaze tracking with general mobile devices and artificial intelligence without dedicated hardware for eye tracking. We conducted experiments to prove that the results can be expressed as quantitative indicators for consumer analysis and intuitive information visualization. The proposed method involves pre-processing of gaze data, classification according to the gaze characteristics, processing of interest-specific regions of gazed points, and information dimension. In addition, the proposed method is accessible at a low cost compared with existing methods, which require purchasing, installation, and use of expensive hardware. The proposed method allows a large number of users with general smartphones or tablets to use the mobile commerce environment naturally without time and space limitations in gathering target information. In conclusion, our method can collect and analyze more specific gaze information-based data for large-scale purchasing processes that are previously impossible. KCI Citation Count: 2